Defining Iran: Politics of Resistance By Shabnam J. Holliday (Surrey, UK: Ashgate, 2011, hbk. 180 pages.) (American Journal of Islam and Society, 2012)
Shabnam Holliday’s Defining Iran: Politics of Resistance is a timely investigationof the Iranian national identity. Through careful discursiveanalysis of a number of texts, including primary sources – speeches, statements,and interviews – as well as articles on the Iranian identity in generaland national identity in particular, Holliday seeks to show how discoursesand counter-discourses emerge and shape the ways Iranians imagine anddefine their national identity. Such deconstruction regards texts producedsince the Pahalvis reign as a preface to her main focus on those producedduring and after Seyyed Mohammad Khatami’s presidency. By lookingat the genealogy of tensions and dynamics between Irānīyat (referring topre-Islamic Iran), Islāmīyat (referring to Islam, namely Persian Shi’i), andthe Western influences in defining what it means to be Iranian, Hollidayillustrates the roots of the “contemporary Iranian national identity” and“Iranian cosmopolitanism” (127) ...